Risk Factors for Liver Steatosis in Obese Children and Adolescents - Yu-Cheng Lin; Pi-Feng Chang; Shu-Jen Yeh; Kevin Liu; Hui-Chi Chen (Pediatrics and Neonatology)
Concurrent with the recent rise of the incidence in obesity, nonalcoholic fatty liver disease is increasingly prevalent in childhood. The aim of this study was to identify non-invasive biomarkers for liver steatosis in obese children and adolescents. Methods: We used a cross-sectional study to examine risk factors for liver steatosis in obese children and adolescents. Sixty-nine obese subjects aged 6–17 years were recruited. The diagnosis of liver steatosis was made by liver ultrasonography. Anthropometric, serum biochemical variables, and oral glucose tolerance tests were measured. Results: Thirty-eight (55.1%) subjects had liver steatosis. Elevated alanine aminotransferase levels (> 30 IU/L in boys and >19 IU/L in girls) were found in 27 (71.1%) of the 38 subjects with liver steatosis. In multivariate logistic regression analysis, liver steatosis was associated with waist circumference and the change of plasma glucose level before and after oral glucose tolerance testing (C-OGTT). For every 5 cm increase in waist circumference, there was an odds ratio of 1.391 for predicting liver steatosis (95% confidence interval: 1.009–1.916, p = 0.044). C-OGTT was the only laboratory variable that independently predicted liver steatosis, with an odds ratio of 1.198 (95% confidence interval: 1.022–1.404, p = 0.026) for each 5 mg/dL of increase. Conclusion: In this hospital-based sample of obese children and adolescents, liver steatosis was common. Liver steatosis was positively associated waist circumference and C-OGTT. These findings have implications for screening liver steatosis in obese children and adolescents.